Firms’ Dynamic Capabilities: A Case of Indonesian Telecommunication Company - Apriza, Sari; Utami, Ami Fitri (Bina Nusantara University, 2018)
Based on the concept of dynamic capabilities that were introduced by Teece & Pisano, this research aimed to analyze how did the dynamic capability condition in Company A. This research used a descriptive qualitative method of secondary data from annual report 2013 to 2017 and article in the website. It is found that Company A possesses a dynamically fluctuate dynamic capabilities through their ability to absorptive capability, adaptive capability, and innovative capability. The implementation of dynamic capabilities in Company A depend on top management board member to develop the company’s general strategic move and by this able to maintain the dynamic capability, and Telecommunication company should be able to nurture the whole organizations’ environment which supports the proliferation of this capability to all the members inside. In short, the benefit of this research will give learning point for the business player or practical to deal with the dynamic situation by using a dynamic capabilities perspective.